Development of scientific literacy-based modules to improve IPA class IV learning outcomes - Fahmi, Nurul; Nurlina, Nurlina; Sulfasyah, Sulfasyah (Jurnal Pembangunan Pendidikan: Fondasi dan Aplikasi, 2023)
This study aims to develop valid, effective, and practical student worksheets based on scientific literacy. The type of research used in this study is Research and Development (R & D) with the ADDIE development model. The subjects used in this study were fourth-grade students, totaling 31 students. The instruments used in this study were learning instruments, student worksheets, and data collection instruments, namely validation questionnaires and teacher and student response questionnaires. The analysis of validity based on data filling in the instrument by expert and practitioner tests both in terms of design and material shows that the scientific literacy-based student worksheets are considered very valid. The practicality of student responses to the module includes several aspects. Namely, the instructions for using the module are obtained in an efficient category, and based on their effectiveness, they are obtained in a very effective category with effective category. Based on the results of data analysis shows that student learning outcomes in class IV.